GEOPHYSICAL AND WATER QUALITY INDEX SURVEYS OF GROUNDWATER QUALITY AROUND UGBOR DUMPSITE IN BENIN CITY, EDO STATE, NIGERIA, WEST AFRICA. - Idehen, Osabuohien (JOURNAL OF ADVANCES IN PHYSICS, 2016)
This study takes a look into groundwater quality at Ugbor Dumpsite area using water quality index (WQI), 2-Dimensional (2-D) geophysical resistivity tomography and vertical electric sounding (VES).The geophysical resistivity methods employed revealed the depth to aquifer, the geoelectric layers being made up of lateritic topsoil, clayed sand and sand. Along the trasverse line in the third geoelectric layer of lateral distance of 76 m to 100 m is a very low resistivity of 0.9 to 13 m from a depth range o f about 3 to 25 m beneath the surface- indicating contamination. Water samples were collected and analyzed at the same site during the raining season and during the dry season. The value of water quality index during the raining season was 115.92 and during the dry season was 147.43. Since values at both seasons were more than 100, it implies that the water is contaminated to some extent and therefore poor for drinking purpose. The Water Quality Index was established from important analyses of biological and physico-chemical parameters with significant health importance. These values computed for dumpsite area at Ugbor were mostly contributed by the seasonal variations in the concentrations of some parameters, such as, conductivity, total dissolved solids, hardness, alkalinity, chlorides, nitrates, calcium,Â  phosphates, zinc, which showed significant differences (P<0.01 and P<0.05) in seasonal variation.